Comparison of Fiberoptic Bronchoscopy versus Landmark Technique for the quick insertion of Percutaneous Dilatation Tracheostomy Tub - Kashif, Sanum; Burki, Ahmed; Tassadaq Syed, Fatima (Pakistan Armed Forces Medical Journal, 2026)
Objective: To Compare Fiberoptic Bronchoscopy (FOB) versus Landmark technique for the quick insertion of Percutaneous Dilatation Tracheostomy Tube (PCDT). Study Design: Quasi-experimental study. Place and Duration of Study: Surgical ICU, Combined Military Hospital, Rawalpindi Pakistan, from Aug 2024 to May 2025. Methodology: Patients were randomly divided into two groups via lottery method. In Group-A, Fiberoptic Bronchoscopy used for PCDT and in Group-B, Landmark technique was used for the insertion of PCDT tube. Correct placement of the endotracheal tube was ascertained by the chest x-ray in both the groups. The primary outcome was the procedural time of successful airway establishment and Secondary outcomes included complications (bleeding, hypoxia and esophageal injury). Results: A total of 78 patients were included in the study. Procedural time was significantly longer in Fiberoptic Bronchoscopic group as compare to Landmark technique group (vs. 18.4±8.1 versus 12.9±4.7 min, p<0.01). Complications including, Bleeding (>50 mL) 15% in Group-A versus 9% in Group-B, Hypoxia was observed in 13% in Group-A versus 6% of cases in Group-B, whereas esophageal injury was not found in any of the group. Conclusion: Percutaneous dilatation tracheostomy (PCDT) insertion with a landmark technique demonstrated superior performance in terms of procedural time as well as complications as compared to the fiberoptic bronchoscope technique.